Modelling Sustainable Development Aspects within Inventory Supply Strategies. (18th March 2021) - Bonilla-Enriquez, Gladys; Cano-Olivos, Patricia; Peng, Li-Qun; Gan, Weihua; Martinez-Flores, Jose-Luis; Sanchez-Partida, Diana
Abstract : Nowadays, inventory management is a tool that must be extended to cover all aspects of the supply chain (SC). One of these aspects is Sustainable Development (SD) which emphasizes the balance between economic well-being, natural resources, and society. As inventory involves the use of natural and economic resources, the integration of SD criteria is important for a more efficient and sustainable SC. In this work, the most important SD variables associated with inventory management were identified. These variables were integrated as cost elements within a nondeterministic inventory control model to include SD criteria within inventory supply strategies. Through the assessment of the proposed integrated model, it was determined that, although SD practices involve additional investments, specific practices such as reuse/recycling and government incentives can increase revenue and profits. This is important for the development of government and business strategies to perform sustainable practices.